2018
DOI: 10.1002/adv.22119
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, optimization, and evaluation of polyvinyl alcohol‐based hydrogels as controlled combinatorial drug delivery system for colon cancer

Abstract: The purpose of current research work was to synthesize and evaluate the cross‐linked ternary hydrogels using polyvinyl alcohol (PVA) and two monomers itaconic acid and methacrylic acid. Controlled combinatorial drug delivery systems (CCDDS) were synthesized by free radical solution polymerization method using ethylene glycol dimethacrylate (EGDMA) as cross‐linking agent. 5‐Fluorouracil (5‐FU) and leucovorin calcium (LC) were loaded in combination into synthesized gels for colonic delivery. Various characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Furthermore, the shape of spleen cells remained unaltered in both control as well as treated group with β-CD-g-poly (MAA) nanocomposite networks. Various researchers from Pakistan have already conducted toxicity studies to ensure safety of living systems against developed crosslinked networks ie, β-CD-g-MAA hydrogel microparticles (Mahmood et al, 2016), polyvinyl alcohol and itaconic acid–g–MAA combinatorial networks (Orva et al, 2018), cellulose acetate phthalate–g–MAA networks (Shah et al, 2018), and chondroitin sulfate–g–MAA (Barkat et al, 2018) etc 34–36. Our results were comparable with the findings of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the shape of spleen cells remained unaltered in both control as well as treated group with β-CD-g-poly (MAA) nanocomposite networks. Various researchers from Pakistan have already conducted toxicity studies to ensure safety of living systems against developed crosslinked networks ie, β-CD-g-MAA hydrogel microparticles (Mahmood et al, 2016), polyvinyl alcohol and itaconic acid–g–MAA combinatorial networks (Orva et al, 2018), cellulose acetate phthalate–g–MAA networks (Shah et al, 2018), and chondroitin sulfate–g–MAA (Barkat et al, 2018) etc 34–36. Our results were comparable with the findings of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to obtain the optimum monomer sequence or number of cross‐links to yield the desired properties; hence combinatorial synthesis can be used. In combinatorial synthesis, a series of different compositions of monomers, modifiers, cross‐linkers, and so forth, can be used 164,165 …”
Section: Resultsmentioning
confidence: 99%
“…Thus, NCHs can be used safely for oral delivery of TG due to their non-toxic nature. 16,22,26 The pharmacokinetic evaluation revealed that C max of both NCH1 and NCH2 showed a 6.5 and 7.2 fold increment, respectively. T max increased from 2 hrs (pure TG) to 6 hrs for both NCH formulations.…”
Section: Discussionmentioning
confidence: 99%